2021
DOI: 10.1523/eneuro.0045-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Unique Effects of Social Defeat Stress in Adolescent Male Mice on the Netrin-1/DCC Pathway, Prefrontal Cortex Dopamine and Cognition

Abstract: For some individuals, social stress is a risk factor for psychiatric disorders characterized by adolescent onset, prefrontal cortex (PFC) dysfunction and cognitive impairments. Social stress may be particularly harmful during adolescence when dopamine (DA) axons are still growing to the PFC, rendering them sensitive to environmental influences. The guidance cue Netrin-1 and its receptor, DCC, coordinate to control mesocorticolimbic DA axon targeting and growth during this age. Here, we adapted the accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 65 publications
7
14
0
Order By: Relevance
“…Experience-induced regulation of Netrin-1 and/or DCC expression robustly shapes the adolescent brain. Social defeat stress in adolescence, but not in adulthood, downregulates Dcc expression in the VTA of male mice, disrupts PFC DA innervation, and leads to cognitive control deficits in adulthood (Vassilev et al, 2021 ). Mild traumatic brain injury in mid-adolescent male mice reduces Netrin-1 expression in the NAc and alters mesocorticolimbic DA organization (Kaukas et al, 2020 ).…”
Section: Mechanisms Underlying Mesocorticolimbic Dopamine Circuit Organization In Adolescencementioning
confidence: 99%
“…Experience-induced regulation of Netrin-1 and/or DCC expression robustly shapes the adolescent brain. Social defeat stress in adolescence, but not in adulthood, downregulates Dcc expression in the VTA of male mice, disrupts PFC DA innervation, and leads to cognitive control deficits in adulthood (Vassilev et al, 2021 ). Mild traumatic brain injury in mid-adolescent male mice reduces Netrin-1 expression in the NAc and alters mesocorticolimbic DA organization (Kaukas et al, 2020 ).…”
Section: Mechanisms Underlying Mesocorticolimbic Dopamine Circuit Organization In Adolescencementioning
confidence: 99%
“…Secondly, we have not queried the potential influence of age on resilience, susceptibility and the role of the BNST in this context. Our defeat stress paradigm was carried out in adults; several studies have demonstrated that it can also be applied during adolescence, when the brain is still developing and highly sensitive to the effects of stress (Iñiguez et al, 2016; Shimizu et al, 2020; Vassilev et al, 2021). Lastly, the rodent BNST is composed of approximately 20 different subregions with a highly diverse population of cell types with subregional specificity (Ortiz‐Juza et al, 2021; Turesson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Husemoen et al [52], Zhang et al [53], Hartz et al [54], Słomiń ki et al [55], Johansson et al [56], sPan et al [57], Lopez-Sanz et al [58], Grant, [59], Słomiń i et al [60], Galán et al sk [61], Jordan et al [62], Winkler et al [63], Yip et al [64], Crookshank et al [65], Lempainen et al [66], Qu and Polychronakos, [67], Morrison et al [68], Zhang et al [69], Gerlinger-Romero et al [70], Belanger et al [71], Dieter et al [72], Wanic et al [73], Ushijima Wanic et al [74], Guo et al [75], Davis et al [76], Elbarbary et al [77], Villasenor et al [78], Zhang et al [79], Lee et al [80], Zhi et al [81], Li Calzi et al [82], Sebastiani et al [83], Cherney et al [84], Doggrell, [85] and Yanagihara et al [86] found that FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N-methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 are involved in the progression of T1DM. Vassilev et al [87], Qin et al [88], Ma et al [89], West et al [90], Hoffmann et al [91], Deary et al [92], Belangero et al [93], Jung et al [94], Tang et al [95], Goodier et al [96], Petyuk et al [97], Roux et al [98], Castrogiovanni et al [99], Suleiman et al [100], Haack et al [101], Kwiatkowski et al [102], Pinacho et al [103], Luo et al [104], He et al [105], Moudi et al [106], Thevenon et al [107], Li et al [108], Reitz et al [109], Jenkins and Escayg [110], Letronne et al [111], Ma et al [112], Chabbert et al [113], Abramsson et al [114], Aeby...…”
Section: Discussionmentioning
confidence: 99%